Phenolic profiles of in vivo and in vitro grown Coriandrum sativum L. - Barros, Lillian (2012)
Coriandrum sativum L. is a source of a variety of polyphenols and other phytochemicals, related to its high antioxidant activity and to its use for indigestion, rheumatism, and prevention of lipid peroxidation damage. Plant cell cultures are a means to study or to produce some active metabolites such as polyphenols. This technique was applied to the investigation of coriander, and a detailed analysis of individual polyphenols in vivo and in vitro grown samples was performed. The in vivo vegetative parts showed quercetin derivatives as the main flavonoids and quercetin-3-O-rutinoside (3296 mg/kg dw) was the main polyphenol found in this part of coriander. The fruits revealed only phenolic acids and derivatives, being caffeoyl N-tryptophan hexoside (45.33 mg/kg dw) the most abundant phenolic derivative. In vitro samples also gave a high diversity of polyphenols, being C-glycosylated apigenin (2983 mg/kg dw) the main compound. Anthocyanins were only found in clone A, which was certainly related to its purple pigmentation, and peonidin-3-O-feruloylglucoside-5-O-glucoside was the major anthocyanin found (1.70 µg/kg dw). In vitro culture can be used to explore new industrial, pharmaceutical and medicinal potentialities, such as the production of secondary metabolites like flavonoids.